Self-assembly of metallosupramolecular rhombi from chiral concave 9,9’-spirobifluorene-derived bis(pyridine) ligands - Hovorka, Rainer; Hytteballe, Sophie; Piehler, Torsten; Meyer-Eppler, Georg; Topić, Filip; Rissanen, Kari; Engeser, Marianne; Lützen, Arne (Beilstein Journal of Organic Chemistry, 2014)
Two new 9,9’-spirobifluorene-based bis(4-pyridines) were synthesised in enantiopure and one also in racemic form. These ligands act as concave templates and form metallosupramolecular [(dppp)2M2L2] rhombi with cis-protected [(dppp)Pd]2+ and [(dppp)Pt]2+ ions. The self-assembly process of the racemic ligand preferably occurs in a narcissistic self-recognising manner. Hence, a mixture of all three possible stereoisomers [(dppp)2M2{(R)-L}2](OTf)4, [(dppp)2M2{(S)-L}2](OTf)4, and [(dppp)2M2{(R)-L}{(S)-L}](OTf)4 was obtained in an approximate 1.5:1.5:1 ratio which corresponds to an amplification of the homochiral assemblies by a factor of approximately three as evidenced by NMR spectroscopy and mass spectrometry. The racemic homochiral assemblies could also be characterised by single crystal X-ray diffraction.
Keywords: concave templates; metal complexes; self-assembly; self-sorting; 9,9’-spirobifluorene; supramolecular chemistry